SISTEM KOMPENSASI BAGI PEMERIKSA PAJAK: MEREDUKSI TAX–EVASION, TINJAUAN DALAM PERSPEKTIF TEORI KEAGENAN (Fokus Ekonomi, 2008)
This paper examines individual and corporate tax evasion in the context of the contractual relationship between the shareholders of a firm and fiskus who possesses private information regarding the extent of legally permissible reductions in taxable income, and who may also undertake illegal tax evasion. The papper try to offer optimal incentive compensation contract for fiskus  and, in particular, how the form of that contract changes in response to alternative enforcement policies imposed by the taxing authority. The optimal contract may adjust to offset, at least partially, the effect of sanctions against illegal evasion, and penalties imposed on fiskus are more effective in reducing evasion than are those imposed on shareholders. Key words : Tax Evasion, Fiskus, Agency Theory